Aplastic Anemia: A literature Review - Maringka, Kezia Michella Yusak; Lestarini, Ima Arum (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Aplastic anemia (AA) is a rare but serious hematologic disorder characterized by bone marrow failure, leading to pancytopenia and a reduction in all blood cell lines. This study aims to explore the definition, etiology, pathophysiology, diagnosis, and treatment of AA. A comprehensive literature review was conducted using electronic databases such as PubMed, ProQuest, ScienceDirect, MDPI, and Google Scholar, focusing on studies and reviews related to AA. The findings indicate that the primary causes of AA include immune-mediated destruction of hematopoietic stem cells, with potential triggers such as drugs, chemicals, and autoimmune disorders. The diagnosis is confirmed through clinical evaluation, blood tests, and bone marrow biopsy. Treatment strategies consist of immunosuppressive therapy, hematopoietic stem cell transplantation (HSCT), and supportive care. In conclusion, early diagnosis and appropriate treatment are essential for improving the prognosis of patients with AA.